IMPROVING THE CITIZEN EXPERIENCE IN THE USE OF MEXICAN GOVERNMENT WEBSITES - del Rio, Marta Sylvia (European Scientific Journal, ESJ, 2014)
Current Mexican government sites lack any commons structure, catalogue of services, use of language or information requirements. State sites can be citizens oriented for a term, and an opposing party might completely change the sites objectives and become a platform for political propaganda on the next term. The motivation for websites to improve was a ranking recently abandoned. This ranking was focused mostly on technical functionality (chats, calendar, navigation) instead of the use of these tools. This paper describes the most common problems found on sites and explains the need for a new ranking that focuses on the quality of information, the amount of screen space used for functionality and the interaction of citizens with its government departments.